ANALISIS PROGRAM TAHFIDZ QUR'AN DENGAN METODE TAWAZUN DALAM PENINGKATAN KUALITAS HAFALAN SISWA DI BOARDING SCHOOL SMA PLUS JABAL RAHMAH MULIA MEDAN - Fitri, Nabilah Nur; Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the implementation of the Qur'an memorization program using the tawazun method to enhance students' memorization quality at SMA Plus Jabal Rahmah Mulia Medan. The research employs a qualitative method with a case study approach. Data collection techniques include in-depth interviews with the school principal, Qur'an teachers, and students, observations of the learning process, and documentation to support the obtained data. Data analysis is conducted using thematic analysis, which involves organizing data, coding, and identifying themes. To ensure data validity, the study applies source triangulation and member checking. The research findings indicate that the Qur'an memorization program implemented with the tawazun method successfully improves students' memorization quality. Students not only excel in memorizing but also understand the meanings and contexts of the verses they memorize. Regular evaluations provide a positive overview of students' progress, although some challenges, such as time constraints and motivation, are identified. The steps taken to address these challenges demonstrate the school's commitment to providing quality education, enabling the Qur'an memorization program to have a significant impact on students' character and spiritual development.